Beyond the beats: exploring the link between blood pressure fluctuations with anxiety, depression, and sleep - Lutchman, Yuvthi; Cosh, Suzanne M.; Cossey, Fiona; Turnbull, Deborah A.; Byrt, Rosannah; Sundaraja, Cassandra; Agarwal, Rakesh; Mahajan, Rajiv; Tzourio, Christophe; Beltrame, John F.; Tully, Phillip J. (Frontiers in Psychiatry, 2025)
IntroductionBlood pressure variability (BPV) is a marker of vascular and autonomic regulation, and emerging evidence links BPV with anxiety and depression. Limited research has explored central BPV, and secondly whether sleep modulates the association between BPV with anxiety and depression.Study designEighty-eight adults from clinical and community settings underwent 24-hour ambulatory blood pressure monitoring to assess central and brachial BPV, including augmentation index (AIx), mean arterial pressure (MAP), and pulse pressure (PP). Psychological symptoms were evaluated using the Generalized Anxiety Disorder Scale (GAD-7), Patient Health Questionnaire (PHQ-9), and Sleep Condition Indicator (SCI). Correlation and regression analyses were conducted, adjusting for age and gender. Mediation analyses explored the role of sleep disturbances in BPV-mood relationships.ResultsHigher central BPV was associated with lower anxiety symptom severity, for somatic and cognitive symptoms (e.g., trouble relaxing: rs = -0.28, p < 0.01), whereas brachial BPV showed minimal associations. No significant relationships emerged between BPV and depressive symptoms after adjustment. AIx demonstrated significant negative associations with sleep-related issues, with stronger effects seen when adjusting for age and gender (β = -0.04, p < 0.01). Mediation analysis revealed sleep-related issues partially mediated the BPV-anxiety relationship.DiscussionFindings suggest that central BPV is more strongly associated with cognitive and somatic anxiety symptoms than depressive symptoms, with sleep disturbances potentially mediating this relationship. These results support BPV’s role in autonomic dysfunction, emphasizing the need for longitudinal research to clarify its role in mental health.